31.6k views
4 votes
Simplify the following expression:

2x − 6y + 3x2 + 7y − 14x.

3x2 + 12x + y
3x2 − 12x − y
3x2 − 12x + y
3x2 − 12x − 13y

2 Answers

3 votes

Answer:

3x2 - 12x + y

Explanation:

User Facetcounter
by
5.7k points
2 votes

Answer:


3x^2 -12x+y

Explanation:

Given expression,


2x - 6y + 3x^2 + 7y - 14x


=(2-14)x + (-6 + 7)y + 3x^2


=-12x + y + 3x^2


\implies 2x - 6y + 3x2 + 7y - 14x=3x^2 -12x+y

Since, further simplification is not possible,

Hence, THIRD option is correct.

User Yanghaogn
by
5.9k points